VITADIAL “Does correction of 25 OH-VITAmin D with cholecalciferol supplementation increase muscle strength in hemoDIALysis patients?”: study protocol for a randomized controlled trial - Bataille, Stanislas; Pedinielli, Nathalie; Carreno, Elisa; Prezelin-Reydit, Mathilde; Chauveau, Philippe; Jean, Guillaume; Robert, Thomas; Bobot, Mickaël; Seret, Guillaume; Jouve, Elisabeth; Lavainne, Frederic; Serveaux, Marianne; et al. (Current controlled trials in cardiovascular medicine, 2021)
Background Muscle strength decreases as kidney failure progresses. Low muscle strength affects more than 50% of hemodialysis patients and leads to daily life activities impairment. In the general population, numerous studies have linked low 25OH-vitamin D (25OHD) concentrations to the loss of the muscle strength and low physical performances. Data on native vitamin D and muscle function are scarce in the chronic kidney disease (CKD) population, but low 25OHD levels have been associated with poor muscle strength. We present in this article the protocol of an ongoing study named VITADIAL testing if cholecalciferol supplementation in hemodialysis patients with low 25OHD improves their muscle strength. Methods/design VITADIAL is a prospective open randomized French multicenter study. All patients will have 25OHD levels ≤50nmol/L at randomization. One group will receive 100,000 UI cholecalciferol once a month during 6 months; the other group will receive no treatment during 6 months. In order to randomize patients with 25OHD ≤50nmol/L, supplemented patients will undergo a 3 months wash-out period renewable 3 times (maximum of 12 months wash-out) until 25OHD reaches a level ≤50nmol/L. The main objective of this study is to analyze if a 6-month period of oral cholecalciferol (i.e., native vitamin D) supplementation improves muscle strength of hemodialysis patients with low 25OHD vitamin D levels. Muscle strength will be assessed at 0, 3, and 6 months, by handgrip strength measured with a quantitative dynamometer. Secondary objectives are (1) to analyze 25OHD plasma levels after vitamin D wash-out and/or supplementation, as well as factors associated with 25OHD lowering speed during wash-out, and (2) to analyze if this supplementation improves patient’s autonomy, reduces frailty risk, and improves quality of life. Fifty-four patients are needed in each group to meet our main objective. Discussion In the general population, around 30 randomized studies analyzed the effects of vitamin D supplementation on muscle strength. These studies had very different designs, sizes, and studied population. Globally, these studies and the meta-analysis of studies favor a beneficial effect of vitamin D supplementation on muscle strength, but this effect is mainly found in the subgroup of aged patients and those with the lowest 25OHD concentrations at inclusion. We reported a positive independent association between 25OHD and handgrip strength in a population of 130 hemodialysis patients in a dose-dependent manner. In our cohort, a plateau effect was observed above 75 nmol/L. Only two randomized studies analyzed the effect of native vitamin D supplementation on muscle strength in hemodialysis patients, but unfortunately, these two studies were underpowered. VITADIAL is a trial specifically designed to assess whether cholecalciferol might benefit to hemodialysis patient’s muscle strength. Trial registration ClinicalTrials.gov NCT04262934 . Registered on 10 February 2020 - Retrospectively registered.